A case of childhood tuberculosis from late mediaeval Somerset, England. (May 2021) - Dawson-Hobbis, H.; Taylor, G.M.; Stewart, G.R.
Abstract: Background: The remains of a 3-5 year-old child from the late mediaeval cemetery serving the Priory of St. Peter and St. Paul, Taunton, Somerset, UK was the subject of an aDNA study. Objective: The aim was to distinguish between two differential diagnoses suggested by earlier osteological examination of the remains; either tuberculosis or Langerhans cell histiocytosis. Findings: The remains tested positive for MTB complex markers, corroborating this diagnosis reached on osteological grounds. Based on positivity for the mtp40 element and a deletion in the pks15/1 locus, we conclude that infection was due to a strain of the human pathogen M. tuberculosis belonging to lineage 4 . Although DNA recovered from the case was heavily fragmented, sex determination by amelogenin PCR suggested these are the remains of a young male child. The findings are discussed considering additions to the literature since the original report. Conclusions: Descriptions of tuberculosis in children from this period are rare and burial Sk2077 represents the first UK example of a pre-adolescent individual to have a molecular diagnosis combined with osteological pathology. This provides an important reference of childhood tuberculosis and insight into the likely presence of tuberculosis in the mediaeval adult population served by this cemetery.